OUTPATIENT PRE-ADMISSION AND AFTERCARE FOR PATIENTS WITH DEPRESSIVE AND ANXIETY DISORDERS: PRELIMINARY RESULTS FROM AN AUSTRIAN CLINIC - Salem, Ingrid; Gaugeler, Richard; Renner, Walter (European Scientific Journal, ESJ, 2014)
Outpatient pre-admission and aftercare is in common use for inpatients with addictive and post-traumatic disorders but is rarely offered to patients suffering from depression or anxiety. Thus, this pilot study has installed and evaluated psychological pre-admission and aftercare on a group basis for patients who had sought inpatient treatment of depression or anxiety at an Austrian psychosomatic clinic. Outpatient pre-admission care aimed at supporting patients ahead of admitting them to the clinic. During the first year of the project N = 59 patients (N=37 or 63% of them female) with a mean age of 47.7 years (s = 11.1 years) participated in pre-admission care. A statistically significant reduction of clinical symptoms was achieved as indicated by the Brief Symptom Inventory (BSI), although in most cases symptoms were still clinically relevant and necessitated inpatient admissions. After leaving outpatient care, two steps of aftercare (ten weekly group sessions each) were supplemented by assertiveness trainings, relaxation, or psycho-education in coping with stress. Older patients were offered special programs ("60+"). During Step 1, aggregated data from regular and 60+ groups (N = 100, 71 female, mean age 53.1, s = 13.1), indicated that symptom reduction achieved during the inpatient stay had been maintained. During Step 2, results from N = 36 patients, (N = 28 female, mean age 53.1, s = 11.6) pointed to a statistically significant reduction of symptoms. The findings suggest providing aftercare for a period of at least 20 week to patients with anxiety or depression.